The Effects of Gender Based Violence on Academic Performance of Learners in Selected Primary Schools in Buyanja Sub-County, Rukungiri District. - Katushabe, Aster (Kabale University, 2024)
The study investigated the impact of gender-based violence on the academic performance of learners in selected primary schools in Buyanja Sub-county, Rukungiri District. It was guided by three objectives: to identify the forms of domestic violence in Buyanja Sub-county, Rukungiri District, to determine the impact of gender-based violence on pupils' academic performance in the selected primary schools, and to propose measures to curb gender-based violence in Buyanja Sub-county, Rukungiri District. The study targeted a population of 60 respondents, including pupils, parents/guardians, and teachers. Simple random and purposive sampling techniques were employed to identify the sample size. Data collection methods included questionnaires, observation, and interviews. The collected data was edited, coded, entered into a computer, and analyzed using Excel, with the results presented in tables. According to the study, 100% of the respondents acknowledged the existence of various forms of domestic violence in the Buyanja Sub-county, Rukungiri District. The common forms included economic abuse (30%), physical abuse (26.6%), and sexual abuse (20%). The study revealed the impact of gender-based violence on the well-being of people in Buyanja Sub-county, Rukungiri District, which included low self-esteem and lack of confidence (21.6%), physical health consequences (16.6%), negative coping mechanisms, social isolation, gender stereotypes, and discrimination (13.3% each). The third objective found that respondents from Buyanja Sub-county suggested several measures to curb gender-based violence, such as understanding the specific root causes of GBV in each community, believing and supporting survivors, engaging men as allies, challenging gender norms, and paying special attention to high-risk groups. The research concluded that various forms of domestic violence in Buyanja Sub-county, Rukungiri District, negatively affect the academic performance of pupils in schools. It recommended further studies on the impact of domestic violence on pupils' academic performance in Buyanja Sub-county, Rukungiri District.